1724 Inexpensive Homemade Agar-Based Models for Ultrasound-Guided Central Venous Catheterization Training Programs. (October 2012) - Pozzi, N; Scoppa, A; Orfeo, L
Abstract : Background and Aims: Central venous catheterization (CVC) plays a central role in patient management in intensive care settings. Compared with the use of traditional anatomical landmarks, ultrasound (US)-guidance is associated with higher success rate and fewer mechanical complications. In order to implement the use of US-guided CVC in our Neonatal and Paediatric Intensive Care Unit, we organized a hands-on training program based on the use of agar-handmade models. Methods: Two different models were constructed to simulate vessels, as described by S. Di Domenico et al in Journal of Ultrasound (2008). In model A the vessels were visualized under a flat surface in both transverse and longitudinal scans, whereas in model B the vessels were punctured under a curved surface and the Doppler function was demonstrated. The training session began with a 40-minute lecture followed by the hands on session. We trained 10 paediatric intensivists. Each test was considered completed when participants were able to position the needle correctly on the "first attempt". Results: 60% of trainees correctly positioned the needle at the first test on model A, whereas only 20% on model B because of the more complicated technique. The percentage of participants who achieved correct needle position increased steadily with repeated punctures showing a quick acquisition of the basic skills of US-guided puncture. Conclusions: Agar-based models are useful tools for teaching the basic hand-eye coordination skills of ultrasound-guided CVC thus reducing hazardous attempts on real patients and facilitating the introduction of this technique in clinical practice.